Multi‐analytical characterization of perigonadal fat in bluefin tuna: from waste to marine lipid source. (17th April 2019) - Saliu, Francesco; Magoni, Chiara; Lasagni, Marina; Della Pergola, Roberto; Labra, Massimo
Abstract: BACKGROUND: Marine lipids are widely recognized as supplements beneficial to health in the human diet. Bluefin tuna, as most migrating fish, may have high and variable marine lipid contents in their tissues. The viscera of the specimens caught in the Mediterranean Sea are generally discarded. Only ovaries are (locally) used for artisanal seafood preparations. RESULTS: A multi‐analytical approach carried out using infrared (IR), nuclear magnetic resonance (NMR) and mass spectrometry (MS) revealed that the perigonadal fats usually discarded during bluefin tuna evisceration are characterized by a high relative abundance of polyunsaturated triacylglycerols (76.2% of dry mass), with docosahexaenoic (DHA, 22:6) and eicosapentaenoic (EPA, 20:5) acids preferentially located at the sn ‐2 position of the glycerol backbone. By contrast, in fats from the ovarian tissues, no wax esters and phospholipids were evidenced. Cholesterol was found in very low amounts (84 mg/100 g ovarian tissue). In vitro assays showed that this fatty material is rapidly hydrolyzed by lipase and is prone to auto‐oxidation, especially if compared to the stable wax esters contained in the ovary. CONCLUSION: The results show that the perigonadal fats of bluefin tuna, traditionally wasted after evisceration, may be an interesting source for the preparation of marine lipid supplements that do not require complex fractionation processes. © 2019 Society of Chemical Industry